Comparative evaluation of pathogenicity of three isolates of vesicular stomatitis virus (Indiana serotype) in pigs. (25th September 2019) - Morozov, Igor; Davis, A. Sally; Ellsworth, Steven; Trujillo, Jessie D.; McDowell, Chester; Shivanna, Vinay; Dasen, Emily J.; Nichols, Richard; Martin, Brian K.; Monath, Thomas P.; Richt, Jurgen A.
Abstract : Vesicular stomatitis (VS) is a notifiable disease of livestock affecting cattle, horses, pigs and humans. Vesicular stomatitis virus (VSV) serotypes Indiana and New Jersey are endemic to Central America; however, they also cause sporadic and scattered outbreaks in various countries in South and North America, including the USA. In order to develop an effective experimental challenge model for VSV, we compared the pathogenicity of three VSV serotype Indiana isolates in 36 4–5 week-old pigs. Two bovine isolates of Central American origin and one equine isolate from the USA were used for the experimental infections. Each pig was inoculated with a single isolate by both the intradermal and intranasal routes. Clinical signs of VSV infection were recorded daily for 10 days post-inoculation (days p.i.). Nasal and tonsillar swab samples and blood were collected to monitor immune responses, virus replication and shedding. Post-challenge, characteristic signs of VS were observed, including vesicles on the nasal planum and coronary bands, lameness, loss of hoof walls and pyrexia. Pigs inoculated with the Central American isolates showed consistently more severe clinical signs in comparison to the pigs infected with the USA isolate. Genomic RNA was isolated from the original challenge virus stocks, sequenced and compared to VSV genomes available in GenBank. Comparative genome analysis demonstrated significant differences between the VSV isolate from the USA and the two Central American isolates. Our results indicate that the Central American isolates of VSV serotype Indiana used in this study are more virulent in swine than the USA VSV serotype Indiana isolate and represent good candidate challenge strains for future VSV studies.